Confirming the safety instrumented system layer of protection. Issue 1 (29th June 2019) - Chastain‐Knight, Denise
Abstract: The safety instrumented system (SIS) is a complex protection layer with high reliability requirements. Assuring the effectiveness of the SIS requires monitoring the effectiveness of the safety instrumented functions (SIFs) as well as the independent protection layer(s) (IPL) that reduce demand on the SIF(s). An SIF tripping more frequently than anticipated may be due to flaws in IPLs intended to reduce demand on the SIF. A slower than expected or failed SIF trip may be due to flaws in the SIF components, the proof testing program, the maintenance program, or inadequate SIF design. This article will identify parameters that should be routinely monitored, illustrate how data can be captured and analyzed, detect weaknesses in the SIS IPL, and provide recommendations for routine monitoring and audit activities.